Biocatalysis for green chemistry and chemical process development - Tao, Junhua; Kazlauskas, R. J. (Romas J.), 1956- (Hoboken, N.J. : John Wiley & Sons, 2011)
This book describes recent progress in enzyme-driven green syntheses of industrially important molecules. The first three introductory chapters overview recent technological advances in enzymes and cell-based transformations, and green chemistry metrics for synthetic efficiency. The remaining chapters are directed to case studies in biotechnological production of pharmaceuticals (small molecules, natural products and biologics), flavors, fragrance and cosmetics, fine chemicals, value-added chemicals from glucose and biomass, and polymeric materials. The book is aimed to facilitate the industrial applications of this powerful and emerging green technology, and catalyze the advancement of the technology itself.
. Overview of biotechnology tools for green synthesis: enzymes, cells and their tunability by engineering -- How green can the industry become with biotechnology -- Emerging enzymes and their synthetic applications -- Reaction efficiencies and green chemistry metrics of biotransformations -- Application and case studies -- pharmaceuticals and fine chemicals -- Biocatalytic routes to chiral intermediates for development of drugs -- Transglutaminase for protein drug modification: pegylation and beyond -- Microbial production of plant-derived pharmaceutical natural products through metabolic engineering: artemisinin and beyond -- Toward greener therapeutic proteins -- Application and case studies? flavor & fragrance, agrochemicals and fine chemicals -- Opportunities for biocatalysis in the flavor, fragrance and cosmetic industry -- Application of biocatalysis in the agrochemical industry -- Green production of fine chemicals by isolated enzymes -- Whole cell production of fine chemicals and intermediates -- Application and case studies? polymers and renewable chemicals -- Green chemistry for the production of biodegradable, biorenewable, biocompatible polymers -- Enzymatic degradation of lignocellulosic biomass -- Bioconversion of renewables-plant oils -- Microbial bioprocesses for industrial scale chemical production.
Includes bibliographical references and index.
Print version record.
Keywords: Green chemistry; Enzymes -- Biotechnology; Green technology; SCIENCE -- Biotechnology; Enzymes -- Biotechnology; Green chemistry; Green technology; Electronic books; Electronic resource; Electronic books